Bacteriophage applications : historical perspective and future potential /: historical perspective and future potential. (2016) - Nicastro, Jessica; Wong, Shirley; Khazaei, Zahra; Lam, Peggy; Blay, Jonathan; Slavcev, Roderick A
No abstract available